Problems of Maharah Al-Qira'ah Learning at MTs Al-Khairaat Gorontalo City - I. Miolo, Mukhtar; Jannah Langkau, Miftahul (Yayasan Daarul Qimmah Gorontalo, 2023)
This study aims to analyze how the process of learning Arabic in class VIII c for the 2021/2022 school year in which there is planning, implementation. And the evaluation of this study also aims to find out how problematic it is in learning Mahara Qiraah at Mts Alkhairaat Gorontalo City in class VIII c. This research is a field research, namely qualitative research. By using data collection techniques, interviews, observations, and documentation of Wawanacara to teachers and students related to problems that occur in Arabic language learning, especially in learning mahara qira'ah. Observations were made to find out how the learning process of mahara qira'ah. Documentation to obtain data related to the general description of the location where the research is located. The results of this study showed that in general the learning of mahara qira'ah in class VIII c went quite smoothly but found some problems faced by students. The problems in learning mahara qira'ah as found in the research location consist of two aspects. The first is the lingustic aspect and the second is non-lingustic. Problems in terms of lingustics are as follows: 1) students find it difficult to pronounce makhorijul letters that match the nature of the letters, (2) students find it difficult to distinguish pronunciation that is almost similar while in non-lingustic aspects; 1) lack of student motivation in learning mahara qiraah (2) preparation of lesson plans that are not optimal (3) strategies used by teachers are still ineffective.